Redefining the Impact of Boltzmann Analysis in the stereochemical assignment of polar and flexible molecules by NMR calculations - Zanardi, María Marta (2019)
Fil: Zanardi, María M. Pontificia Universidad Católica Argentina. Facultad de Química e Ingeniería del Rosario; Argentina